(untitled) (Journal of Science & Technology, 2021)
Root cause analysis (RCA) is an indispensable process in managing and maintaining the reliability of complex IT systems, where incident resolution times directly influence operational efficiency and service availability. Traditional RCA methods, although robust, are often constrained by their reliance on static heuristics and manual expertise, leading to inefficiencies in addressing incidents within highly dynamic environments. This paper explores the integration of machine learning (ML) techniques to enhance RCA processes, focusing on accelerating incident resolution and improving system reliability. By leveraging supervised, unsupervised, and reinforcement learning paradigms, ML-driven RCA provides actionable insights by automatically identifying causal relationships within vast and heterogeneous datasets. Such methodologies facilitate the prioritization of incident factors, enabling IT teams to mitigate issues more effectively. The study outlines key machine learning models tailored for RCA, including decision trees, random forests, support vector machines, and neural networks, alongside their respective roles in anomaly detection, classification, and causal inference. Particular emphasis is placed on the application of graph-based learning and Bayesian networks to model complex dependencies between system components, thereby enhancing interpretability and diagnostic accuracy. Furthermore, this paper examines the synergy between ML-enhanced RCA and existing observability tools such as monitoring systems, log analyzers, and distributed tracing mechanisms. Integration with these tools ensures the continuous ingestion and processing of high-velocity data streams, a critical requirement for real-time RCA in modern IT ecosystems. A detailed evaluation of case studies demonstrates the efficacy of ML-driven RCA in environments such as cloud computing platforms, microservices architectures, and software-defined networks (SDNs). These case studies highlight significant reductions in mean time to resolution (MTTR) and an increase in overall system uptime. For example, the deployment of anomaly detection algorithms in a multi-cloud environment identified latent performance bottlenecks and prevented cascading failures, showcasing the proactive capabilities of ML-based solutions. Despite its potential, the adoption of ML-enhanced RCA is not devoid of challenges. This research addresses key hurdles, including data quality issues, the need for domain-specific feature engineering, and the computational overhead associated with real-time processing of large-scale datasets. It also explores ethical considerations, particularly in contexts where RCA decisions may impact critical business operations or user experience. Solutions to these challenges are proposed, ranging from hybrid ML approaches to the implementation of interpretability techniques such as SHAP (Shapley Additive Explanations) values and LIME (Local Interpretable Model-Agnostic Explanations) to foster trust in automated diagnostic processes.